Decomposition Mechanism of Lignin Models on Pt(111) : Combining Single Crystal Experiments and First-Principles Calculations - Ould Hamou, Cherif Aghiles (Université d'Ottawa / University of Ottawa, 2019)
The world energy and product consumption keep increasing steadily over the years as the world population keeps growing and more countries become industrialized. As the world reserves deplete it becomes a necessity to find an alternative way to meet the population’s demand. Biomass conversion seems to be the future of a clean and sustainable world. Lignin is the second most abundant polymer in the biomass. Given the unique structure and chemical properties of lignin, a wide variety of bulk and fine chemicals can be obtained and be used for goods and biofuels production. Catalysis, with its selective bond cleavage and lower energy activation, is considered as a potential key solution in the process of lignin conversion into valuable chemicals. To gain insights into that catalytic system, we performed surface science experiments (X-ray Photoelectron Spectroscopy, Temperature Programmed Desorption and Reflection Absorption Infrared Spectroscopy) under Ultra-High Vacuum conditions (UHV). Due to lignin’s physical properties limitation under UHV conditions, lignin models with the same chemical structure such as phenol, anisole, 2-phenoxyethanol and veratrol were used to gain a better understanding of the reactivity of lignin itself. Dosing anisole and 2-phenoxyethanol on Pt(111) surprisingly gave benzene, carbon monoxide and hydrogen as the main desorbing products of decomposition. With the help of Density Functional Theory (DFT), we successfully explain the unexpected selectivity. In the present work, we show in particular that phenoxy PhO stands as a key intermediate. Although the UHV conditions do not allow the hydrogenation of phenoxy into phenol, i.e. the catalytic product, they reveal the key role of both hydrogen and carbonaceous species. Under UHV conditions, anisole and 2-phenoxyethanol are extensively dehydrogenated: it results in the formation of carbonaceous fragments, which can actually perform the deoxygenation of phenoxy into benzene. The reactivity of veratrol on Pt(111) hindered the formation of benzene and only gave carbon monoxide and hydrogen as the main desorbing products of decomposition. Although carbonaceous fragments were formed on the surface, the deoxygenation of the two oxygenated arm moieties does not occur without the total decomposition of the aromatic ring, hence the formation of coke. This detailed work opens the door to a rational design of metal-based catalysts and a route towards lignin valorization.
Keywords: Lignin; Biomass; Pt(111); Anisole; XPS; TPD; DFT; RAIRS; Catalysis; 2-Phenoxyethanol